In-depth evaluation of laser-welded similar and dissimilar material tab-to-busbar electrical interconnects for electric vehicle battery pack. (October 2021) - Kumar, Nikhil; Masters, Iain; Das, Abhishek
Abstract: A recent increase in the use of electric vehicles demands an efficient and faster joining process for making electrical interconnects within the battery pack. The choice of tab and busbar materials to produce those electrical interconnects is mainly based on weldability, weight, electrical/ thermal conductivity and cost. To meet the high joining demand and low cycle time, laser welding is emerging as the main joining technology due to its ability to weld a variety of materials at a high speed. This paper investigates laser overlap welding for producing similar and dissimilar material tab-to-busbar interconnects for Li-ion battery assembly. In this research, 0.3 mm Al, Cu, Cu[Ni] and Ni tabs were welded with 1.5 mm Al and Cu busbars using a 150 W pulsed fibre laser system integrated with a wobble head. The weldability and joint suitability analyses were conducted by evaluating joint strength, joint intermetallic compound (IMC) formation, joint resistance and temperature rise with the aim of developing a better and safer battery system. It was observed that a maximum joint strength of 930 N was obtained from the Ni tab to Al busbar joints which was approximately 109%, 44% and 66% more than the strength obtained for Al, Cu[Ni] and Cu tab to Al busbar joints respectively. In the case of Cu busbar based tab connections, the maximum joint strength (1320N) was obtained from the Ni tab, which is 152%, 71% and 76% more than Al, Cu[Ni], and Cu tab to Cu busbar joint strength respectively. The strength obtained for the Cu tab to Al busbar (about 560 N) was slightly more than the Al tab to Cu busbar (about 520 N) due to the formation of CuAl2 IMCs at the weld interface of Al tab to Cu busbar joints. Weld microstructure studies provided insightful information on under-weld, good-weld and over-weld characterisation with respect to IMC formation and correlated with the joint strength. In addition, electrical resistance and temperature rise at the joint are equally important for electric vehicle battery applications. The change in contact resistance and joint temperature rise was measured simultaneously for 180 s at different amplitudes of current (i.e., 100 A, 150 A and 200 A) passed through the joints. Highlights: Joining and selection of suitable tab and busbar materials for producing electrical interconnects for EV batteries In-depth analysis on laser-welded Al, Cu, Cu[Ni] and Ni tab to Al and Cu busbar joints were performed Joint suitability analyses were conducted by evaluating joint strength, intermetallic, resistance and temperature rise The results on critical-to-quality criteria should guide the battery manufacturers to design an efficient battery system